Determinants of retinopathy of prematurity: A prospective observational study from Tertiary Care Teaching Hospital from North India - Gupta, Ashok K; Pandita, Neerul; Gupta, Surbhi; Sharma, Ashok K (Indian Journal of Child Health, 2014)
Objective: This prospective observational study was designed to evaluate the point prevalence as well as various risk factors associated with retinopathy of prematurity (ROP) in preterm/low birth weight (LBW) babies <32 weeks of gestation and or birth weight ?1500 g on both inborn and outborn babies. Materials and Methods: Binocular opthalmological examination was performed 4-6 weeks postnataly under local eye anesthesia in 200 newborns who qualified the above criteria. If ROP was detected, the 2nd evaluation was done after 1 week, 3rd evaluation after 2 weeks and 4th after 4 weeks. The examination was carried out by the same ophthalmologist. Results: 25 (12.5%) out of 200 babies developed ROP. 23 were in Stage 1 and 2 in Stage 2 at first evaluation. All showed regression, i.e., they had completed temporal vascularization on repeat follow-up evaluations. No baby showed progression to threshold stage at any time of follow-up examinations. On multiple logistic regression analysis, factors having significant association with development of ROP were birth weight (p = 0.0028), oxygen therapy (p = 0.0059), septicemia (p = 0.0062), and blood transfusion (p = 0.0013). Conclusion: In our study, point prevalence of ROP was 12.5 % (25/200) which is substantially high among preterm/LBW babies. Thus, evaluation for ROP should be done mandatorily in all preterm/LBW babies, particularly with gestation <32 weeks and or weight ?1500 g and when risk factors are present, so as to prevent the long-term morbidity which ranges from mild myopia to blindness.